WIYN open cluster study: The old open cluster, NGC 188, and a re-evaluation of Lithium-richness among red giants. Issue 4 (10th May 2022) - Sun, Qinghui; Deliyannis, Constantine P; Twarog, Bruce A; Anthony-Twarog, Barbara J; Cummings, Jeffrey D; Steinhauer, Aaron
ABSTRACT: We present WIYN 1 /Hydra spectra of 34 red giant candidate members of NGC 188, which, together with WOCS 2 and Gaia data yield 23 single members, 6 binary members, 4 single non-members, and 1 binary non-member. We report [Fe/H] for 29 members and derive [Fe/H]NGC188  = +0.064 ± 0.018 dex (σμ ) (sky spectra yield A(Fe)⊙  = 7.520 ± 0.015 dex (σμ )). We discuss effects on the derived parameters of varying Yale-Yonsei isochrones to fit the turnoff. We take advantage of the coolest, lowest gravity giants to refine the line list near Li 6707.8 Å. Using synthesis we derive detections of A(Li) 3  = 1.17, 1.65, 2.04, and 0.60 dex for stars 4346, 4705, 5027, and 6353, respectively, and 3σ upper limits for the other members. Whereas only two of the detections meet the traditional criterion for 'Li-richness' of A(Li) > 1.5 dex, we argue that since the cluster A(Li) vanish as subgiants evolve to the base of the RGB, all four stars are Li-rich in this cluster's context. An incidence of even a few Li-rich stars in a sample of 29 stars is far higher than what recent large surveys have found in the field. All four stars lie either slightly or substantially away from the cluster fiducial sequence, possibly providing clues about their Li-richness. We discuss a number of possibilities for the origin for the Li in each star, and suggest potentially discriminating future observations.